2020
DOI: 10.1515/rams-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cd and SPD on structure, physical, mechanical, and operational properties of alloy of Cu-Cr-Zr

Abstract: An increase in the service life of electrical products from copper and its alloys is directly related to an increase in the wear resistance of materials. Structural refinement and alloying with cadmium are known to have a positive effect on the strength characteristics and wear resistance of copper, which makes it possible, with a Cd content of 1% by weight, to increase the wear resistance of copper several times, but cadmium is considered an environmentally unsafe element. In this regard, the paper presents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Hence, both adhesive and abrasive wear mechanism are observed. The amount of wear is correlated to the rise in temperature and contact pressure on sliding interfaces; similar results were reported by researchers [7,8,20]. An increase in temperature may cause localized welding, which leads to severe plastic deformation/ploughing under sliding conditions.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Hence, both adhesive and abrasive wear mechanism are observed. The amount of wear is correlated to the rise in temperature and contact pressure on sliding interfaces; similar results were reported by researchers [7,8,20]. An increase in temperature may cause localized welding, which leads to severe plastic deformation/ploughing under sliding conditions.…”
Section: Resultssupporting
confidence: 80%
“…The newly developed alloy system exhibits excellent thermal stability at 400 • C, surpassing the thermal stability of cadmium bronzes by a factor of two. Additionally, this alloy system demonstrates significantly improved wear resistance compared to the existing Cu alloys [20,21].…”
Section: Introductionmentioning
confidence: 97%
“…For example, its flow stress during deformation at high temperatures should be significantly reduced, and at the same time, there are also excellent applications in the field of superplasticity [10,11]. Recently, a series of reports showed that SPD could produce materials that combine high strength and high ductility [12,13]. More importantly, because UFG materials have smaller characteristic sizes that are orders of magnitude smaller than in micro-parts, they can significantly reduce the "scale effect" of the micro-forming processing.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Cu-Cr-Zr alloy has become a research hotspot in recent decades due to its advantages to meet these requirements, [4][5][6][7] and previous researchers have shown its importance in the high-speed rail network. 2,6,[8][9][10][11][12] Cu-Cr-Zr alloy used in contact wires are usually produced by semi-continuous casting and cold working. [13][14][15][16] Since cold deformation introduces dislocations, twinning and residual stress, which are considered to be important during preparation process for improving the strength of materials.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of high‐speed electrified railways, researchers showed increasing interest in higher requirements for the performance of contact line materials (higher strength, higher conductivity, higher anti‐softening temperature and good plasticity) 1–3 . Cu‐Cr‐Zr alloy has become a research hotspot in recent decades due to its advantages to meet these requirements, 4–7 and previous researchers have shown its importance in the high‐speed rail network 2,6,8–12 …”
Section: Introductionmentioning
confidence: 99%